Paget’s disease of the breast: Our 20 years’ experience - Scardina, Lorenzo; Di Leone, Alba; Magno, Stefano; Franco, Antonio; Biondi, Ersilia; Sanchez, Alejandro Martin; D’Archi, Sabatino; Gentile, Damiano; Fabi, Alessandra; Masetti, Riccardo; Franceschini, Gianluca (Frontiers in Oncology, 2022)
INTRODUCTION Paget's disease (PD) represents 1-3% of all breast cancers and mostly occurs in postmenopausal women. Multiple studies have confirmed that breast conserving surgery (BCS) followed by radiotherapy is a safe option for patients with in situ or invasive PD, ensuring local control and survival rates similar to those achieved with mastectomy. MATERIALS AND METHODS We retrospectively analyzed 115 patients affected by PD treated in our Institution between January 2000 and May 2021. Median age at diagnosis was 60 years and median follow-up 82 months; 69 patients were treated with breast conserving surgery (BCS) and 46 with modified radical mastectomy or skin sparing mastectomy. RESULTS At histological examination 59 patients (59/115 - 51.0%) had an underlying invasive carcinoma; in 11 patients (11/115 – 9.0%), only PD was found. In 45 patients (45/115 – 40.0%) was found a non-invasive cancer alone. Nine patients (9/115 – 7.8%) developed a local recurrence, 7 patients (7/115 – 6.0%) are alive with distant metastasis and 10 patients (10/115 – 8.6%) died. DISCUSSION In our series no statistically differences were shown between PD alone, PD associated with in situ or PD with invasive cancer, regardless of the surgical procedure. BCS followed by radiotherapy appears to be an effective and safe option for patients with PD. CONCLUSION Paget’s Disease is a rare form of breast cancer and in half of cases is associated with an invasive carcinoma. Separating our sample into three subgroups based on tumor histology there were no significant differences in term of LC, DFS and OS rate in patients treated with different type of surgery. This study presents some limitations due to its retrospective nature and being confined to a single institution.